The reality of the heroic graduate students from the College of Physical Education and Sports Sciences - University of Baghdad for the academic year 2022/2023 - Muhamed, Bashar; Salam, Karam; Kamal, Ali (Journal of Physical Education, 2023)
The hero student is considered a distinguished student in a particular sport, excelled and worked hard in it, and won medals in honor of his time and effort to obtain them. Graduates from the college, numbering (32) students, who were chosen by the deliberate method, The researchers used the descriptive approach to achieve the aim of the research, and the researchers used a questionnaire consisting of two axes, and the frequency and percentage were calculated. The rest of the categories accepted in the college to serve its students.